MicroRNA162 regulates stomatal conductance in response to low night temperature stress via abscisic acid signaling pathway in tomato - Li, Yangyang; Liu, Yang; Gao, Zhenhua; Wang, Feng; Xu, Tao; Qi, Mingfang; Liu, Yufeng; Li, Tianlai (Frontiers in Plant Science, 2023)
MicroRNAs (miRNAs) mediate the degradation of target mRNA and inhibit mRNA translation to regulate gene expression at the transcriptional and post-transcriptional levels in response to environmental stress in plants. We characterized the post-transcriptional mechanism by deep sequencing small RNA (sRNA) to examine how miRNAs were involved in low night temperature (LNT) stress in tomato and whether the molecular mechanism depended on the abscisic acid (ABA) signaling pathway. We annotated conserved miRNAs and novel miRNAs with four sRNA libraries composed of wild-type (WT) tomato plants and ABA-deficient mutant (sit) plants under normal growth and LNT stress conditions. Reverse genetics analysis suggested that miR162 participated in LNT resistance and the ABA-dependent signaling pathway in tomato. miR162-overexpressing (pRI-miR162) and miR162-silenced (pRNAi-miR162) transgenic tomato plants were generated to evaluate miR162 functions in response to LNT stress. miR162 deficiency exhibited high photosynthetic capacity and regulated stomatal opening, suggesting negative regulation of miR162 in the ABA-dependent signaling pathway in response to LNT stress. As feedback regulation, miR162 positively regulated ABA to maintain homeostasis of tomato under diverse abiotic stresses. The mRNA of DICER-LIKE1 (DCL1) was targeted by miR162, and miR162 inhibited DCL1 cleavage in LNT response, including the regulation of miRNA160/164/171a and their targets. The DCL1-deficient mutants (dcl1) with CRISPR/Cas9 prevented stomatal opening to influence photosynthesis in the ABA signaling pathway under LNT stress. Finally, we established the regulatory mechanism of ABA-miR162-DCL1, which systematically mediated cold tolerance in tomato. This study suggests that post-transcriptional modulators acted as systemic signal responders via the stress hormone signaling pathway, and the model at the post-transcriptional level presents a new direction for research in plant abiotic stress resistance.